Practical .NET 2.0 Networking Projects - Lee, Wei-Meng (Apress, 2012)
Practical .NET 2.0 Networking Projects demonstrates some of the key networking technologies that are being made easily accessible through the .NET Framework 2.0. It discusses communication between wired machines and between networks and mobile devices. The book teaches you about the technologies by walking you through sample projects in a straightforward and direct way. This book contains six chapters, each covering a specific aspect of network programming. You’ll use the various APIs within the .NET Framework as well as third-party SDKs to build a variety of cutting-edge networking applications that cover everything from Bluetooth and RFID communication to sockets programming and chat servers. You’ll build working examples for each project, which you can also customize and use for your own purposes. The featured projects cover the following.